Economic and Social Analysis of Abaca Fiber MSME Actors’ Welfare: A Case Study in Talaud Islands Regency - Jola Silvana Kalangi; Julita Inggrine Nelwan; Yopie A. T. Pangemanan; Jane Elvira Scipio; Royke Max Suot; Sjerly Maria Lumi; Lenda Lumenta; Lalira, James (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study examines the economic and social determinants of welfare among Abaca fiber-based micro, small, and medium enterprise (MSME) actors in the Talaud Islands Regency in Indonesia. Despite the global recognition of abaca fiber for its durability and sustainability (used in currency notes, luxury automotive interiors, and marine ropes), local producers continue to experience severe welfare challenges. Employing a mixed-methods approach with a sequential explanatory design, data were collected through a structured survey of 30 entrepreneurs and in-depth interviews supported by field observations and focus group discussions. Findings reveal a significant decline in abaca enterprises, particularly in Essang, where 87% of respondents classify their business as “declining” or “newly initiated.” The average monthly income from this activity ranges between IDR 40,000 and IDR 60,000, deemed insufficient by 93% of the respondents to meet basic household needs. Income instability, driven by fluctuating demand and exploitative pricing by intermediaries, has reduced enterprises to marginal, non-primary livelihoods. Structural fragmentation of the value chain, absence of formal market access, and lack of postharvest support following initial government incentives have further weakened sustainability. While 77% of producers involve family or neighbors in production, indicating latent social capital, collaboration among artisans remains minimal, with 60% reporting rare or competitive interactions. Although 87% expressed a strong interest in training and institutional support, only 13% received direct financial assistance. The study concludes that the persistence of poverty among abaca producers is not due to commodity value but to systemic inequities in market access, institutional neglect, and policy discontinuity. Strategic interventions, such as collective marketing institutions, digital promotion, technological training, and inclusive partnerships, are recommended to transform abaca MSMEs into a sustainable and empowering sector.